MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SDIT ISHLAHUL UMMAH KOTA SAWAHLUNTO - Hamadi Hamadi (IAIN Batusangkar, 2018)
This study aims, to describe the principal's plan to improve teacher performance in SDIT Ishlatul Ummah, Sawahlunto City, to describe the organization of principals in improving teacher performance at SDIT Ishlatul Ummah in Sawahlunto City, to describe the implementation of principals in improving teacher performance in SDIT Ishlatul Ummah Kota Sawahlunto, and to describe the supervision of the principal in improving teacher performance at SDIT Ishlatul Ummah in Sawahlunto City. The research method is qualitative research with a case study method or approach. Research informants were 6 people. Data collection tools are researchers as key instruments and supporting instruments are interview guidelines, observation guidelines, field notes, and hand pone (HP). Data collection techniques are participatory observation, in-depth interviews and documentation studies. Data analysis techniques use the Miles and Huberman model which divides data analysis into three, namely data reduction, data presentation, and conclusion drawing. Data validity testing techniques using data triangulation and method triangulation. The results showed that starting from planning, organizing, implementing and supervising the principal program in improving teacher performance such as improving discipline, providing motivation, holding teacher training in schools, supervising or supervising teacher performance, fostering teacher performance, and establishing cooperative relationships with teachers , it has been going well done by the school principal to improve teacher performance in achieving the educational goals at SDlah Ishlahul Ummah in Sawahlunto City.